Victimology and victim rights: international comparative perspectives - Kirchengast, Tyrone (Routledge, 2017)
Victim issues in international law and context -- International norms in victimology and victim rights -- Comparative issues and perspectives -- Victims in international law and policy -- Victims in regional law and policy -- Victims in domestic law and policy -- Victim rights in law and policy -- Victim rights in the twenty-first century : intervention and innovation